2007
DOI: 10.1089/thy.2006.0141
|View full text |Cite
|
Sign up to set email alerts
|

Surgery versus Radioiodine Therapy as Definitive Management for Graves' Disease: The Role of Patient Preference

Abstract: One-third of all patients electing surgery as definitive management do so in the absence of a specific indication. Overall, there is a high level of satisfaction with the decision for surgery as definitive management of Graves' disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 19 publications
4
32
0
Order By: Relevance
“…Therefore for patients with larger goiter and higher 99m Tc-pertechnetate uptakes, a calculated dose based on size and uptake is perhaps a better decision [12]. Surgical treatment (partial thyroidectomy) is also a reasonable option in such cases, as it propitiates prompt relief of symptoms related to compression of the esophagus and/or trachea [13]. …”
Section: Discussionmentioning
confidence: 99%
“…Therefore for patients with larger goiter and higher 99m Tc-pertechnetate uptakes, a calculated dose based on size and uptake is perhaps a better decision [12]. Surgical treatment (partial thyroidectomy) is also a reasonable option in such cases, as it propitiates prompt relief of symptoms related to compression of the esophagus and/or trachea [13]. …”
Section: Discussionmentioning
confidence: 99%
“…The complication rates are usually higher for patients with GD and thyroiditis due to the increased vascularity and inflammation of the gland. Studies have reported complication rates of 6-20% for transient hypocalcaemia, 0-3% for permanent hypocalcaemia, 0-9.2% for transient RLN injury, and 0-2.4% for permanent RLN injury [12,20,21,22,23,24]. In our study, patients with robotic surgery had a complication rate of 8.3% for temporary hypocalcaemia, but there were no cases of permanent hypocalcaemia or RLN injury.…”
Section: Discussionmentioning
confidence: 41%
“…In recurrent hyperthyroidism, thyroidectomy is a valid alternative to RAI according to patient choice [ 29 ]. Thyroid surgery should be performed by skilled and experienced surgeons to minimize the risk of related complications, namely, hypoparathyroidism and laryngeal nerve paralysis [ 30 ].…”
Section: Thyroidectomymentioning
confidence: 99%